2019
DOI: 10.1101/614511
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preclinical immunoPET imaging of glioblastoma-infiltrating myeloid cells using Zirconium-89-labeled anti-CD11b antibody

Abstract: Purpose. Glioblastoma is a lethal brain tumor, heavily infiltrated by tumor-associated myeloid cells (TAMCs). TAMCs are emerging as a promising therapeutic target as they suppress antitumor immune responses and promote tumor cell growth. Quantifying TAMCs using non-invasive immunoPET could facilitate patient stratification for TAMC-targeted treatments and monitoring of treatment efficacy. As TAMCs uniformly express the cell surface marker, integrin CD11b, we evaluated a 89 Zr-labeled anti-CD11b antibody for no… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…TAMCs account for up to 40% of a glioma's cellular mass and play an important role in tumor progression, immunosuppression, and resistance to immunotherapy [4][5][6]. Numerous preclinical studies by us and others have demonstrated that targeting TAMs and MDSCs can prolong survival of mice with gliomas [5,[7][8] and that these cells are associated with poor prognosis in high-grade gliomas [9]. Since TAMCs impede natural and immunotherapy-driven anti-tumor responses, they are a highpriority and promising therapeutic target currently being evaluated in clinical trials [7][8]10] .…”
Section: Introductionmentioning
confidence: 99%
“…TAMCs account for up to 40% of a glioma's cellular mass and play an important role in tumor progression, immunosuppression, and resistance to immunotherapy [4][5][6]. Numerous preclinical studies by us and others have demonstrated that targeting TAMs and MDSCs can prolong survival of mice with gliomas [5,[7][8] and that these cells are associated with poor prognosis in high-grade gliomas [9]. Since TAMCs impede natural and immunotherapy-driven anti-tumor responses, they are a highpriority and promising therapeutic target currently being evaluated in clinical trials [7][8]10] .…”
Section: Introductionmentioning
confidence: 99%
“…773,774 Accumulating evidence has suggested that immunoPET imaging may substantially improve the clinical immunotherapy by dynamically visualizing immune responses across the whole body. 775−777 To achieve this goal, radiotracers have been developed to image interleukins and specific immune cells, including B cells, 778 natural killer cells, 779,780 macrophages, 781−783 myeloid cells, 278,784 and T cells. In this section, we mainly present the most recent evidence of immunoPET strategies in delineating T cells by targeting lineage-associated antigens, immune checkpoint molecules, OX40, and interferon gamma (IFNγ).…”
Section: Immunopet Imaging Of Immune Systemmentioning
confidence: 99%
“…Mice were anesthetized by mask inhalation of 1.5% vaporized isoflurane throughout the surgical procedure. GL261 cells (100,000 cells in 2 mL DPBS) were stereotactically implanted into the caudate nucleus using the following coordinates relative to bregma: x = +2.5 mm (lateral), y = +1.5 mm (anterior), and z = 2-3.0 mm (inferior) (33). MRI was performed 7 days post tumor cell implantation to confirm tumor presence, and again at day 40 to measure tumor size growth in control-treated animals and aTIGIT & aPD1 dual blockade-treated animals.…”
Section: Intracranial Tumor Model and Antibodies Treatmentmentioning
confidence: 99%